The ECB's Inflation Objective - Kieler, Mads. (Washington, D.C. : International Monetary Fund, 2003)
The ECB's objective of medium-term inflation below 2 percent has been portrayed by critics as ambiguous, asymmetric, and excessively stringent. This paper attempts a comprehensive evaluation of the trade-offs for the euro area and finds that: (1) in terms of guiding inflation expectations and policymaking, the current definition has functioned much as would an inflation target centered on 1 1/2-1 3/4 percent; (2) the absence of a specific (point) target for medium-term inflation has encumbered the communication of monetary policy; and (3) a target toward the upper end of the ECB's price-stability range would seem, at least with the current membership of EMU, to strike a judicious balance between the benefits of price stability, on the one hand, and the need to assist relative price and wage adjustment across EMU and safeguard against deflation, on the other hand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet